The impact of sending top college graduates to rural primary schools - Masyhur A. Hilmy (Asian Development Bank Institute (ADBI), 2022)
Teacher quality is crucial to deliver good education. However, improving teacher quality in developing countries can be a tough problem. This paper investigates the impact of a teacher placement program that sends college graduates with a strong academic track record to teach in rural primary schools in Indonesia on student test scores. Using a difference-in-difference approach, we find that exposure to program teachers for a semester is associated with a 0.16 standard deviation increase in their students' average mathematics scores. The weakest students benefited more, with an increase in score by 0.20 standard deviation. Students receiving direct instructions from program teachers during scheduled classroom periods benefited even more. Attracting better talents to teach in rural schools could be an important pathway to improve the academic achievements of the weakest students at rural schools.
Keywords: F4; E5; C3; 330; US monetary policy; foreign spillovers